Evaluation of factors affecting tumor response and survival in patients with primary and metastatic liver cancer treated with microspheres. Issue 4 (April 2015) - Demirelli, Serkan; Erkilic, Metin; Oner, Ali Ozan; Budak, Evrim Surer; Gunduz, Seyda; Ozgur, Ozhan; Bozcuk, Hakan; Sindel, Hakki Timur; Boz, Adil
Abstract : Objective: Radioembolization with the yttrium-90 (Y-90) microspheres is being used increasingly more often in the treatment of patients with primary or metastatic liver cancer. Although technetium-99m macroaggregated albumin (Tc-99m MAA) scintigraphy performed following diagnostic angiography has an important role in predicting the effectiveness of treatment and in dose estimation, the number of studies using quantitative assessment of Tc-99m MAA scintigraphy is limited in this field. In the present study, the aim was to assess whether a tumor dose is required to obtain objective tumor response and to check whether this threshold value is predictive in terms of tumor response, survival, and liver toxicity by using Tc-99m MAA single-photon emission computed tomography (SPECT) images. Materials and methods: Overall, 54 patients (20 women and 34 men; median age: 60 years) who underwent Y-90 Resin (SIR-Spheres) and Glass (TheraSphere) microsphere treatment with a diagnosis of unresectable liver cancer between August 2010 and April 2013 were included in the study. The mean doses to normal liver and tumor were estimated for each patient using Tc-99m MAA SPECT images and the medical internal radiation dosimetry method. The responses were assessed according to Response Evaluation Criteria In Solid Tumors (RECIST) and European Organisation for Research and Treatment of Cancer (EORTC) criteria. Kaplan–Meier survival curves and univariate Cox regression analysis were used in survival analysis. The relationship between treatment response and other parameters included was assessed using logistic regression analysis. The variables with a P value less than 0.01 in univariate analysis were assessed with multivariate analysis. Results: Fifty-four Y-90 microsphere treatments (eight by using a Y-90 glass microsphere and 46 by using a Y-90 resin microsphere) were performed. In the multivariate analysis, the only parameter related to response was tumor dose ( P <0.01). With a tumor dose of 280 Gy or higher, objective tumor response was observed in 59 and 77% of the patients according to RECIST and EORTC criteria, respectively, and the tumor control rate was found to be 95% according to both criteria. In addition, it was found that only tumor dose was correlated with progression-free survival (PFS) ( P <0.001) and overall survival (OS) ( P =0.018). When the tumor dose was 280 Gy or higher, median PFS increased from 2 to 10.7 months ( P <0.001), whereas median OS increased from 9 to 17.6 months ( P =0.018). However, reversible ≥G2 liver toxicity was observed in 3.7% (2/54) of the patients within 3 months after radioembolization with a median normal liver dose of 40 Gy (10–102 Gy). There was reversible ≥G3 liver toxicity in 3.7% (2/54) of patients, but no G4 liver toxicity was observed. Clinical radiation hepatitis and treatment-induced liver failure were not observed in any of these patients. Conclusion: Tc-99m MAA SPECT has a predictive value in terms of response to radioembolization, PFS, and OS. Dosimetry based on Tc-99m MAA SPECT images can be used in the selection of patients and, in particular, to adaptation of treatment plan in selected patients.